Ascending colon adenocarcinoma with tonsillar metastasis: A case report and review of the literature - Sheng, Li-Ming (The WJG Press and Baishideng, 2008)
Metastatic palatine tonsil cancer is extremely rare, with nearly 100 such tumors reported in the English literature. The prognosis of metastatic palatine tonsil cancer is poor. A 53-year-old man presented with painless left palatine tonsillar swelling and a cervical mass following right hemicolectomy for an ascending colon adenocarcinoma. Physical examination showed an ulcerated mass located on the upper pole of the left palatine tonsil. A punch biopsy was taken for histological examination which showed a moderately-differentiated adenocarcinoma. The patient was treated with palliative radiotherapy and chemotherapy. He was still alive when we wrote this paper. Our case shows that immunohistochemical diagnosis of metastatic palatine tonsil cancer is essential.